2011
DOI: 10.1097/coc.0b013e3181d2734a
|View full text |Cite
|
Sign up to set email alerts
|

Phase II and Coagulation Cascade Biomarker Study of Bevacizumab With or Without Docetaxel in Patients With Previously Treated Metastatic Pancreatic Adenocarcinoma

Abstract: Purpose Treatment options are limited for advanced pancreatic cancer progressive after gemcitabine therapy. The vascular endothelial growth factor (VEGF) pathway is biologically important in pancreatic cancer, and docetaxel has modest anti-tumor activity. We evaluated the role of the anti-VEGF antibody bevacizumab as second-line treatment for patients with metastatic pancreatic cancer. Design Patients with metastatic adenocarcinoma of the pancreas who had progressive disease on a gemcitabine-containing regim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 41 publications
0
22
0
Order By: Relevance
“…The prevalence of D-dimer elevations at baseline and throughout treatment (consistent with the well-recognized association between progressive malignancy, activation of coagulation, and fibrinolysis; refs. [23][24][25][26][27][28], along with a failure to predict thromboembolic events, render this assay noninformative in this population. Accordingly, the ongoing and future studies of bavituximab do not include D-dimer eligibility requirements or monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of D-dimer elevations at baseline and throughout treatment (consistent with the well-recognized association between progressive malignancy, activation of coagulation, and fibrinolysis; refs. [23][24][25][26][27][28], along with a failure to predict thromboembolic events, render this assay noninformative in this population. Accordingly, the ongoing and future studies of bavituximab do not include D-dimer eligibility requirements or monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…Treatments such as the anti-angiogenic agent bevacizumab [8], the Sonic Hedgehog (Shh) inhibitor vismodegib [9] or the EGFR receptor-targeting agent cetuximab [10] produced partial responses or limited stable disease in some individuals, but no statistically significant improvements in the general population of PDAC patients. With 30–41 new drugs granted FDA approval each year for cancer therapy [7], there has been a notable lack of progress in pancreatic cancer, with only 4 new agents becoming available to the patients in the past 20 years.…”
Section: Introductionmentioning
confidence: 99%
“…These regimens included: cisplatin and gemcitabine [46]; capecitabine and gemcitabine [47]; capecitabine, radiation, and gemcitabine [48]; oxaliplatin and gemcitabine [49]; gemcitabine and radiation [50, 51], and docetaxel [52] (Table 1). However, results from the Phase III trial directly comparing bevacizumab plus gemcitabine to placebo plus gemcitabine in advanced PDAC patients showed that the addition of bevacizumab does not result in an improvement in overall survival (OS) or progression free survival (PFS) or differences in the ORR (Table 3) [53].…”
Section: Clinical Studies In Pdacmentioning
confidence: 99%
“…It would be useful if we could identify those patients who might benefit the most via the use of predictive biomarkers. Though some trials have attempted to look for correlations between certain known pro-angiogenic molecules circulating in the plasma and treatment response, none have been successful to date [44, 46, 52, 76]. With an increasing number of studies utilizing high throughput technologies like RNA sequencing (RNA-Seq) to profile human tumors, it is possible that a gene expression signature could be used.…”
Section: Reasons For Failurementioning
confidence: 99%